Peran Manajemen Humas dalam Menarik Minat Calon Peserta Didik di SMKN 1 Pasarwajo Kabupaten Buton - Fera, Fera; Kamaruddin, Syamsu; Basri, Syamsurijal (Universitas Negeri Makassar, 2023)
This study aims to determine the role of public relations management in attracting prospective students at SMKN 1 Pasarwajo. This research method is qualitative with a qualitative descriptive research type. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. The results showed that 1) The role of public relations as a communicator (liaison) for the internal public through formal meetings and flag ceremonies while for the external public through school profile presentations, student guardian meetings, collaboration with DUDI, and conveying school information to the community, 2) The role of public relations as a relationship builder through formal meeting activities, retirement activities, outreach activities to the community, and also collaboration between DUDI parties, 3) The role of public relations as back up management (management support), namely a) in public relations planning, b) in implementation, c) in the implementation of the evaluation, and 4) The role of public relations as a corporate image for the internal public by creating a conducive atmosphere in schools, and services to the public. As for the external public through social service and participation in community activities.